Disease-modifying antirheumatic drugs in rheumatoid arthritis: current concepts. - Emery, P; Luqmani, R; Gordon, C (1994)
Disease-modifying antirheumatic drugs are used in virtually all patients with established rheumatoid arthritis. An increasingly large number of new drugs is now available. Furthermore, old therapies are being used in novel ways. Treatment is now begun earlier and patients are rarely left untreated. This report summarises recent developments regarding the drugs currently in use and those that may be available in the near future.